From Uncertainty to Confidence: Peer-Led Research and the Formation of Medical Academic Identity - Andrea Cuschieri; Sarah Cuschieri (International Medical Education, 2025)
Background: Undergraduate research is vital for developing critical thinking and academic identity in medical students, yet traditional models often fail to overcome institutional and personal barriers. Peer-led approaches may offer more accessible, supportive environments that promote deeper engagement and leadership in research. Methods: This study evaluated medical students’ experiences in a peer-led research initiative from 2022 to 2024. Students were then invited to complete a qualitative questionnaire reflecting on their perceptions towards research, development in research skills, confidence, and academic identity. Results: Code saturation was achieved after 9 responses (N = 15). Participants reported intrinsic interest, peer encouragement, and opportunities to publish as motivating factors. The peer-led model made research feel more approachable, fostering technical growth and academic confidence. Peer mentorship and a gradual learning structure were especially valued. While challenges such as workload and team dynamics emerged, students reported growth in resilience and self-reflection. Conclusions: Peer-led research initiatives can effectively support academic identity formation by integrating motivation, support, and skill development. Despite obstacles, students gained competence and confidence.